Deviations from the Expectable Environment in Early Childhood and Emerging Psychopathology - Humphreys, Kathryn L (Neuropsychopharmacology, 2015)
Current frameworks for understanding the link between early adverse childhood experiences and later negative life outcomes, including psychopathology, focus on the mediating negative impact on brain and biological systems in the developing child resulting broadly from stress and trauma. Although this approach is useful, we argue that the framework could be functionally extended by distinguishing the effects of two different types of abnormal input, both deviations from the expectable environment in early childhood. Specifically, we review the consequences of inadequate input (eg, neglect/deprivation) and harmful input (eg, abuse/trauma) on brain and biological development. We then review evidence on the differential links between each type of abnormal input to four selected domains of psychopathology (indiscriminate social behavior, posttraumatic stress disorder, attention-deficit/hyperactivity disorder, and conduct problems), and consider potential mechanisms for inadequate and harmful input to lead to these outcomes. We conclude that the careful consideration of the type of deviation from the expected environment, while acknowledging the practical difficulties in assessing this, is likely to lead to clearer understanding of the mechanism of risk for psychopathology, and that tailored approaches to prevention and intervention may be informed by considering the unique consequences of inadequate and harmful input when experienced in early childhood.